Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ueg2.12190
|View full text |Cite
|
Sign up to set email alerts
|

Glucose variability during the early course of acute pancreatitis predicts two‐year probability of new‐onset diabetes: A prospective longitudinal cohort study

Abstract: Background Acute pancreatitis (AP) is the largest contributor to diabetes of the exocrine pancreas. However, there is no accurate predictor at the time of hospitalisation for AP to identify individuals at high risk for new‐onset diabetes. Objective To investigate the accuracy of indices of glucose variability (GV) during the early course of AP in predicting the glycated haemoglobin (HbA1c) trajectories during follow‐up. Methods This was a prospective longitudinal cohort study of patients without diabetes at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…60 Given that oxyntomodulin and amylin showed inverse associations in individuals after AP, the pathophysiological changes that take place after an episode of AP (such as insulin resistance) may modulate the interaction between amylin and oxyntomodulin. [61][62][63][64] The present study had several limitations. First, all blood biomarkers were measured in the fasted state only.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…60 Given that oxyntomodulin and amylin showed inverse associations in individuals after AP, the pathophysiological changes that take place after an episode of AP (such as insulin resistance) may modulate the interaction between amylin and oxyntomodulin. [61][62][63][64] The present study had several limitations. First, all blood biomarkers were measured in the fasted state only.…”
Section: Discussionmentioning
confidence: 85%
“…It is conceivable that an increase in HbA 1c levels 58 and the presence of insulin resistance after AP may cause overexpression of amylin, mitigating its anorexigenic properties 60 . Given that oxyntomodulin and amylin showed inverse associations in individuals after AP, the pathophysiological changes that take place after an episode of AP (such as insulin resistance) may modulate the interaction between amylin and oxyntomodulin 61–64 …”
Section: Discussionmentioning
confidence: 99%
“…Also, the present study included people with a history of acute pancreatitis, 45,46 as the project focusing on this population had received funding. 47,48 Nevertheless, a complete clinical resolution was observed in all study participants at the time of magnetic resonance image acquisition. [20][21][22][23] The protocol to measure IHFD in the present study might have been suboptimal as we did not use T1 and T2 correction of water signal and lipid signal from single echo magnetic resonance spectroscopy data.…”
Section: Discussionmentioning
confidence: 86%
“…regarding blood glucose variability (GV) during the course of acute pancreatitis with great interest. 1 Although it has been shown that around 23% of patients with acute pancreatitis develop diabetes mellitus within 3 years discharge from hospital, 2 , 3 the pathophysiology of acute pancreatitis associated diabetes is poorly understood. However, Bharmal et al.…”
mentioning
confidence: 99%
“…
Blood glucose variability in patients with acute pancreatitisI have read the original article by Bharmal et al regarding blood glucose variability (GV) during the course of acute pancreatitis with great interest. 1 Although it has been shown that around 23% of patients with acute pancreatitis develop diabetes mellitus within 3 years discharge from hospital, 2,3 the pathophysiology of acute pancreatitis associated diabetes is poorly understood. However, Bharmal et al identified increased GV during the course of acute pancreatitis as a risk factor of developing diabetes.
…”
mentioning
confidence: 99%